Principal Managerial Skills in Development Religious Culture at State Elementary School 15 Air Kumbang - Nyamidi Nyamidi; Nur Ahyani; Nila Kesumawati (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2025)
This study aims to determine and describe the principal's managerial skills in developing a religious culture at SD Negeri 15 Air Kumbang. The method used is a qualitative method. Data collection techniques use observation, interviews and documentation. The results of the study can be concluded that the Management of the Principal of SD Negeri 15 Air Kumbang in developing a religious culture is through planning, organizing, implementing, supervising and evaluating. The management carried out by the Principal of SD Negeri 15 Air Kumbang includes: first, the implementation of daily activities in the form of: providing exemplary behavior/examples, reprimands/advice, conditioning the environment that supports character education, routine activities/character habits, and mentoring and supervision activities for character education. Second, the management of the principal of SD Negeri 15 Air Kumbang through programmed activities in the form of: Imtaq activities before starting lessons and completing the Al-Quran every month, dhuha prayer activities, dzuhur prayers in congregation. Third, the Management of the Principal of SD Negeri 15 Air Kumbang through learning activities. In learning activities, religious culture must be implemented which includes the preparation of plans and learning tools that contain religious values.